Evaluación de los sistemas de producción de pequeñas empresas metalúrgicas del cantón Quevedo para mejorar su competitividad - Cuadra Franco, July Genesis (2018)
The present investigation on the evaluation took place in the small metal-mechanic companies of the Quevedo canton, the companies participating in this evaluation on the production systems to improve their competitiveness are, Induhorst, Maindustria, Rectificadora Palma and Rectificadora Pico, these companies were identified according to the Andean Community of Nations (CAN), as small companies according to the number of workers that operate in each one and with the annual sale item. In addition it was possible to determine the strengths, opportunities, weaknesses and threats that they have and that are also key pieces for the proper functioning of the same, without leaving aside the productive system a fundamental area for each of the companies, thanks to the different methods and techniques applied, it was possible to know the production process established by each, as well as to investigate the machines, equipment and tools used to process the product before it reaches its final part. Finally after having made the respective analysis as a whole, it was possible to propose a Manufacturing Strategy Model (MSM) that the respective companies already mentioned could apply so that they can improve their competitiveness, establishing themselves with strength in the metal-mechanic market. national as well as internationally leading to a greater emergence among other companies.